If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -16 = -56 Reorder the terms: -16 + Y = -56 Solving -16 + Y = -56 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + Y = -56 + 16 Combine like terms: -16 + 16 = 0 0 + Y = -56 + 16 Y = -56 + 16 Combine like terms: -56 + 16 = -40 Y = -40 Simplifying Y = -40
| 5-x/10=12 | | n-4=-78 | | log*3(4x-2)=4 | | G(4)=3x^2+1 | | 1-3(9x-6)= | | (x+3)(x-1)=x+x+5 | | 6v-2-7v=-1 | | -14+10= | | 4(2-5x)=-2x-2 | | i=(1152)(.013)(1/12) | | 9c=6c-42 | | q=0.8571428571 | | 4(-11/3) | | x/10-11=9 | | 6x+3x=26 | | 26/3-5=3 | | (7x+15)=3(3x-7) | | 6x-19=7x+6 | | 5+7x=12x | | -3y+x=15 | | f(x)=3x^5-25x^3+60x+10 | | 11p+11=111 | | 4(2-5x)=-2x-27 | | 3D-5=-9+7d | | (0.5x^3)-5=0 | | 9y+12-6y=-18 | | 3g+4=2g+6 | | 2+7(4)=34-4 | | 2+7(5)=34-5 | | 9(1/3x-2)=18 | | 4z/7-3=4 | | -22=-6-4x |